Environmental risk assessment for veterinary antibiotics and hormone in Malaysian agricultural soil - Ho, Yu Bin; Zakaria, Mohamad Pauzi; Abdul Latif, Puziah; Saari, Nazamid (Tehran University of Medical Sciences, 2014)
Background: Repeated applications of animal manure as fertilizer are normal agricultural practices in Malaysia that may release veterinary antibiotics to environment from treated animals. Methods: Environmental risk assessment (ERA) on 5 commonly used antibiotics and one hormone in Malaysian broiler farm was calculated using the ratio of measured environmental concentration (MEC) and predicted no effect concentration (PNEC) in the environment. PNEC was derived from the available acute and chronic toxicity data in the open peer-reviewed literature. Risk quotients (RQ) were then calculated for 5 antibiotics (erythromycin, norfloxacin, sulfadiazine, trimethoprim, and tylosin) and one hormone (progesterone). Results: RQ for tylosin has exceeded 1, indicating that this compound has high risk of acute toxicity in Malaysian agricultural soil while trimethoprim and tylosin possessed medium risk of chronic toxicity. The rest of the compounds showed low risk or no risk in acute or chronic ecological toxicity. Conclusion: The release of tylosin, trimethoprim, norfloxacin and progesterone from broiler manure to agricultural soil may potentially harm the environment.